Traffic Management in the New Commercial Area of Basko City Mall by BPTD Class II West Sumatra - Lutfiah, Viola Putri; Helmi, Rahmadhona Fitri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The growth of commercial areas such as Basko City Mall in Padang has boosted economic activity but also created traffic problems due to high vehicle volumes that reduce road network performance. As a mitigation effort, the West Sumatra Class II Land Transportation Management Center (BPTD) closed the U-turn in front of BCM to minimize traffic flow conflicts, although this policy has sparked both support and criticism from the public. This study aims to describe the traffic management and control conducted by the Land Transportation Management Center (BPTD) Class II of West Sumatra in the new commercial area of Basko City Mall Padang, as well as to identify the internal and external challenges faced by BPTD Class II West Sumatra in managing traffic in the area. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results based on the POAC framework show that BPTD Class II West Sumatra faces two main types of obstacles in traffic management: internal constraints, such as the limited number of certified human resources in Traffic Impact Analysis (Andalalin), and external constraints, such as the lack of effective coordination between related institutions. In terms of Planning, traffic management in the Basko City Mall area is conducted procedurally through Andalalin prepared by certified consultants, with BPTD mainly acting as a supervisor. The Organizing function shows a clear division of roles but limited inter-agency coordination. In the Actuating stage, BPTD implements Andalalin recommendations, such as closing the U-turn, though coordination among institutions remains uneven. Meanwhile, Controlling is carried out through periodic monitoring and forums, but follow-up actions are still limited. These findings highlight the need to strengthen human resource capacity, coordination, and integrated monitoring to improve traffic management effectiveness in new commercial areas.